HEALTH ANXIETY AND PSYCHOLOGICAL WELL-BEING AMONG PHYSICIANS DURING CORONAVIRUS PANDEMIC (KECEMASAN KESEHATAN DAN KESEJAHTERAAN PSIKOLOGIS PADA DOKTER SELAMA PANDEMI VIRUS CORONA) - Fatmawati, Fatmawati - (Psikoislamedia: Jurnal Psikologi, 2022)
COVID-19 pandemic gives several personal impacts on physicians. They reports an increase in cases of stress and anxiety, especially anxiety related to health, which then contributes to their mental health and psychological well-being. Therefore, this study aimed to measure the relationship between health anxiety and psychological well-being among physicians during COVID-19 outbreak. The study was conducted in Aceh Province and there were 338 physicians who participated. The accidental sampling was used in order to gain the participants. The health anxiety was carried out through The Short Health Anxiety Inventory (Abramowitz, Deacon, & Valentiner, 2007), while psychological well-being was measured through Ryff’s Psychological Well-Being Scales (Ryff, 1989). Cronbach’s alphas for the 17 health anxiety items and 42 psychological well-being items were 0.85 and 0.89, respectively. In order to test the hypothesis, Pearson Correlation Test was conducted. From the analysis, it was found that health anxiety and psychological well-being were negative significantly correlated, r=-0.12, p<0.05. This meant the higher health anxiety, the lower psychological well-being among medical doctors, and vice versa. From this study, it could be concluded that health anxiety experienced by physicians had a significant impact on their psychological well-being, therefore, there must be proper support available for all health practitioners (not only physicians) as they are the front-line professional who directly deal with patients during this COVID-19 outbreak. Pandemi Covid-19 memberikan beberapa dampak pribadi bagi para dokter. Mereka melaporkan peningkatan kasus stres dan kecemasan, terutama kecemasan terkait kesehatan, yang kemudian berkontribusi pada kesehatan mental dan kesejahteraan psikologis mereka. Oleh karena itu, penelitian ini bertujuan untuk menganalisis hubungan antara kecemasan kesehatan dengan kesejahteraan psikologis dokter selama wabah Covid-19. Penelitian ini dilakukan di Provinsi Aceh dan sebanyak 338 dokter yang berpartisipasi. Pengambilan sampel dilakukan dengan accidental sampling. Kecemasan kesehatan diukur dengan The Short Health Anxiety Inventory (Abramowitz, Deacon, & Valentiner, 2007), sedangkan kesejahteraan psikologis diukur melalui Ryff's Psychological Well-Being Scales (Ryff, 1989). Alpha Cronbach untuk 17 item kecemasan kesehatan dan 42 item kesejahteraan psikologis masing-masing adalah 0,85 dan 0,89. Untuk menguji hipotesis dilakukan Uji Korelasi Pearson. Dari hasil analisis diketahui bahwa kecemasan kesehatan dan kesejahteraan psikologis berkorelasi negatif secara signifikan, r=-0,12, p<0,05. Ini berarti semakin tinggi kecemasan kesehatan, maka semakin rendah kesejahteraan psikologis di antara para dokter, dan sebaliknya. Dari penelitian ini dapat disimpulkan bahwa kecemasan kesehatan yang dialami oleh dokter memiliki dampak yang signifikan terhadap kesejahteraan psikologis mereka. Oleh karena itu, harus ada dukungan yang tepat untuk semua praktisi kesehatan (tidak hanya dokter) karena mereka adalah profesional garis depan yang langsung menangani pasien selama wabah COVID-19 ini.